Image processing and analysis - Birchfield, Stan (Boston, MA Cengage Learning, 2018)
Gain a firm understanding of image processing as you cover the major topics of the field using a balanced approach that progresses from simple explanations to more detailed descriptions within IMAGE PROCESSING AND ANALYSIS. This easy-to-follow, accessible book emphasizes a basic, fundamental understanding of the classic algorithms in the field while also highlighting recent research results. You can grasp the subtle tradeoffs among different approaches as well as understand them in context with the latest developments in the field. Numerous full-color illustrations and detailed pseudocode bridge the gap between mathematical equations underlying the important concepts and real-world application of those concepts. This understanding makes it easier for you to program your own implementations of these algorithms. In addition, consistent notation throughout this edition makes it easier to follow the various concepts.--Provided by publisher.
Keywords: Image processing; Computer vision; Image analysis